Method for removing oxytetracycline in water body by activating periodate with boron nitride modified copper ferrite

By modifying the copper ferrite to activate periodate by boron nitride, the high energy consumption and interference problems of oleracene in water in the prior art are solved, and efficient, stable and economical removal of oleracene is achieved. Effect.

CN119430428AActive Publication Date: 2025-02-14HUNAN UNIV

Patent Information

Application Number
CN202411592249.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-14
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The prior art has limitations such as high energy consumption and interference with water matrix components when removing oleracin in water bodies, and the reusability and cost of periodate catalytic materials are not ideal.

Method used

The method of activating periodate by modifying boron nitride-modified copper ferrite is used to mix boron nitride-modified copper ferrite with oleracin-containing water, and performing catalytic reaction after adding periodate. Achieve efficient removal of oleracin in water.

Benefits of technology

This method can efficiently remove oleracycin in water under mild reaction conditions, with a removal efficiency of up to 91.02%, and has a wide pH range and anti-environmental interference ability. The catalyst still maintains high degradation after five cycles. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430428A_ABST
    Figure CN119430428A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing oxytetracycline in a water body by activating periodate with boron nitride modified copper ferrite. The catalytic material takes copper ferrite as a main body material and boron nitride as a modification material, and the mass ratio of the boron nitride to the copper ferrite is 1: (5-20). The catalytic material adopted by the invention promotes the transfer of charges through the action of a surface carrier and the formation of an interface Fe-N bond, so that excellent oxytetracycline removal performance is realized. The method for removing oxytetracycline in the water body by activating periodate with boron nitride modified copper ferrite has the advantages of low cost, simple operation, stable catalytic performance, wide applicable pH range, strong anti-interference capability, high oxytetracycline removal efficiency and the like, and has a very good application prospect in oxytetracycline wastewater treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wastewater treatment, and specifically relates to a method for removing oxytetracycline in water by activating periodate with boron nitride-modified copper ferrite. Background Art

[0002] Since the successful development of penicillin in the 1940s, antibiotics have played a vital role in the treatment of human diseases. However, with the application of antibiotics in the fields of medicine, animal husbandry and aquaculture, a large number of antibiotics have entered the environment, causing pollution of water, soil and atmosphere, and adversely affecting the ecosystem. Tetracycline antibiotics (TCs), such as oxytetracycline (OTC), are one of the most widely used antibiotics in the world. Because they are not easily absorbed by organisms, difficult to degrade in the environment, and difficult to completely remove in conventional sewage treatment systems, they pose a serious threat to the ecosystem and human health. In animal husbandry, antibiotics are used as feed additives to improve livestock immunity, promote growth, and improve economic benefits. Most of the metabolites of these antibiotics enter the environment through livestock excrement, causing pollution of rivers and oceans.

[0003] So far, various technologies such as biodegradation, adsorption and advanced oxidation technology (AOPs) have been used to remove and degrade oxytetracycline in water environments. Advanced oxidation technology (AOPs) has shown significant advantages in treating refractory organic matter due to its high efficiency, rapidity, environmental friendliness and no secondary pollution, and has become one of the important technologies in the field of water treatment. Commonly used oxidants in AOPs include: hydrogen peroxide (H2O2), ozone (O3), persulfate (S2O8 2- , PS), potassium permanganate (KMnO4), periodate (IO4 - , PI), etc. These oxidants generate free radicals with strong oxidizing ability, such as hydroxyl radicals (·OH), through different reaction mechanisms in advanced oxidation technology, thereby effectively oxidizing and decomposing oxytetracycline in water.

[0004] As an emerging oxidant, periodate (PI) has attracted attention due to its stability, easy activation ability and high efficiency in decontamination. AOPs based on PI have strong oxidative ability and can efficiently degrade various oxytetracyclines in a wide pH range, and have good application potential in the field of water treatment. PI in AOPs mainly produces reactive oxygen species (such as ·OH, 1 O2 and O2 ·-) and reactive iodine species (such as IO3· and IO4·) to eliminate pollutants. However, the oxidation ability of PI itself is very limited (the reduction potential is +1.6eV). Various activation methods such as light, heat, metal catalysts, and carbon material catalysts have been explored by researchers to enhance the activation ability of periodate and apply it to the treatment of organic wastewater in water bodies. However, the current water treatment technology based on PI AOPs is still limited by high energy consumption and interference from water matrix components. Therefore, seeking a periodate catalytic material with high efficiency, strong anti-interference ability, wide application range, good reusability and low cost is of great significance for the treatment of organic wastewater. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for removing oxytetracycline in water by activating periodate using boron nitride-modified copper ferrite with excellent catalytic performance, high stability, wide application range and environmental friendliness.

[0006] In order to solve the above technical problems, the purpose of the present invention is achieved through the following technical solutions:

[0007] The method for removing oxytetracycline in water by activating periodate with boron nitride-modified copper ferrite is characterized in that the boron nitride-modified copper ferrite activates periodate to degrade oxytetracycline in water; the boron nitride-modified copper ferrite is prepared by in-situ growth of copper ferrite (CuFe2O4) on boron nitride (BN) using copper ferrite (CuFe2O4) as a base material and boron nitride (BN) as a modifying material; the mass ratio of boron nitride to copper ferrite in the boron nitride-modified copper ferrite is 1:5-20. Preferably, the copper ferrite is a three-dimensional nano-spherical structure with a diameter of about 300-500nm; the boron nitride is a two-dimensional porous nano-sheet structure.

[0008] The above method is further improved, wherein the method is to use boron nitride modified copper ferrite to activate periodate to degrade oxytetracycline in water, comprising the following steps: mixing the boron nitride modified copper ferrite with the water containing oxytetracycline for half an hour to achieve the adsorption and desorption equilibrium between the catalyst and oxytetracycline, and further adding periodate to perform an oxytetracycline degradation experiment. The amount of the boron nitride modified copper ferrite added is 0.3g to 0.7g of the boron nitride modified copper ferrite per liter of pollutant solution.

[0009] The above method is further improved, wherein the water body is water containing oxytetracycline; the concentration of the water body containing oxytetracycline is 5-25 mg / L; the pH value of the water body containing oxytetracycline is 3.0-11.0; the periodate in the degradation experiment is sodium periodate (NaIO4); the periodate concentration in the degradation experiment is 0.4-1.2 mM; the time for the catalyst to reach adsorption and decomposition equilibrium is 30-60 min; and the reaction time of the degradation experiment is 0-60 min.

[0010] The above method is further improved, and the preparation method of the boron nitride modified copper ferrite comprises the following steps:

[0011] S1. Disperse boric acid and melamine in a beaker filled with deionized water, heat and dissolve, and stir to obtain a uniform solution. Then put the above solution into a refrigerator to precipitate a white solid, filter and collect the white solid, and further dry to obtain a boron nitride precursor; then, calcine the above boron nitride precursor twice in a tube furnace to obtain boron nitride;

[0012] S2. Ultrasonic dispersion of the boron nitride obtained in step S1 in ethylene glycol, and further stirring to obtain a uniform suspension. Then, add copper nitrate trihydrate and ferric nitrate nonahydrate to the above suspension, stir until completely dissolved, and obtain a transparent reddish-brown solution A; dissolve anhydrous sodium acetate in ethylene glycol and stir evenly to form a white solution B; then, dropwise add solution B to the stirred solution A, and further stir evenly to obtain solution C; finally, transfer the above solution C to a polytetrafluoroethylene reactor for hydrothermal reaction, and separate, wash, and dry the reaction product to obtain a precursor of boron nitride-modified copper ferrite;

[0013] S3, placing the precursor of the boron nitride modified copper ferrite obtained in step S2 in a muffle furnace for calcination to obtain a boron nitride modified copper ferrite.

[0014] The above method is further improved. In step S1, the ratio of melamine, boric acid and water is 0.756g:0.742g:100mL; the ultrasonic time is 30-60min; the heating temperature is 80-90°C; the stirring is carried out at a rotation speed of 500r / min-800r / min; the refrigeration temperature is 0-4°C; the drying treatment is carried out at a temperature of 60°C-80°C; the drying treatment time is 8h-12h; the calcination is carried out under N2 atmosphere; the first calcination temperature is 600°C, the calcination heating rate is 5°C / min, and the calcination time is 3h; the second calcination temperature is 700°C, the calcination heating rate is 5°C / min, and the calcination time is 2h.

[0015] The above method is further improved, in step S2: the mass ratio of the boron nitride and the stoichiometric copper ferrite is: 1:5-20; the ultrasonic time of the solution A is 30-60 min; the ratio of copper nitrate trihydrate, ferric nitrate nonahydrate, anhydrous sodium acetate, and ethylene glycol in the solution C is 1 mmol: 2 mmol: 3 mmol: 15 mL; the stirring time is 30-60 min, and the stirring is carried out at a speed of 500 r / min-800 r / min; the ratio of ethylene glycol content in the solutions A and B is: 7 mL: 2 mL; the stirring time is 30-60 min, and the stirring is carried out at a speed of 500 r / min-800 r / min; the temperature of the hydrothermal reaction is 180-200° C., and the hydrothermal reaction time is 18 h; the solid separation method is magnetic precipitation separation; the drying treatment is carried out at a temperature of 60° C.-80° C.; the drying treatment time is 8 h-12 h.

[0016] The above method is further improved, in step S3: the calcination temperature is 400-450°C, the calcination heating rate is 5°C / min, and the calcination time is 2-3h.

[0017] Compared with the prior art, the advantages of the present invention are:

[0018] (1) The present invention provides a method for removing oxytetracycline from water by activating periodate with copper ferrite modified by boron nitride. By mixing copper ferrite modified by boron nitride with water containing oxytetracycline, and then adding periodate to degrade oxytetracycline, efficient removal of oxytetracycline from water can be achieved. The method has the advantages of simple operation, high pollutant removal efficiency, and no secondary pollution, and has a good application prospect in the field of organic wastewater treatment. Boron nitride modified copper ferrite activated periodate degraded oxytetracycline in water for 60 minutes, which can remove more than 91.02% of oxytetracycline, and can achieve efficient removal of oxytetracycline from water, which is of great significance for the treatment of oxytetracycline-contaminated water.

[0019] (2) The present invention provides a method for removing oxytetracycline from water by activating periodate with copper ferrite modified by boron nitride. By mixing copper ferrite modified by boron nitride with water containing oxytetracycline and then adding periodate for catalytic reaction, efficient removal of oxytetracycline from water can be achieved. The method has a wide pH application range (3.0-11.0) and is suitable for inorganic anions (SO4 2- 、NO3 - 、CO3 2- 、HCO3 - , Cl -) still has good oxytetracycline removal performance under the condition of existence, and has strong resistance to environmental interference. In addition, after five cycles of use, it still has high pollutant degradation performance and has the advantage of high stability.

[0020] (3) In the present invention, the boron nitride modified copper ferrite uses copper ferrite as the main material, and the Fe 2+ / Fe 3+ and Cu + / Cu 2+ The formed bimetallic redox cycle can continuously promote the activation of periodate and the generation of active species such as free radicals, showing good catalytic performance. Boron nitride is used as the modification material, and its porous two-dimensional nanosheet structure has a large specific surface area, which can make copper ferrite evenly dispersed on its surface, effectively solving the problem of copper ferrite agglomeration and inactivation.

[0021] (4) The boron nitride modified copper ferrite described in the present invention can achieve effective dispersion of copper ferrite nanospheres by adjusting the ratio of boron nitride to copper ferrite in the composite material, thereby ensuring effective exposure of active sites in the material, and the porosity and large specific surface area of ​​boron nitride can effectively improve the material's adsorption performance for periodate. At the same time, the nitrogen atoms in boron nitride interact with the metallic iron atoms in the copper ferrite to form a covalent Fe(δ+)-N(δ-) chemical bond. This interfacial chemical bond can serve as an interfacial charge transfer channel, further accelerating the migration of charges and promoting the delocalization of electrons at the center of the iron atom to trigger the catalytic process.

[0022] (5) In the present invention, the method of removing oxytetracycline from water by activating periodate with copper ferrite modified by boron nitride has the advantages of mild reaction conditions, simple process flow, and easily controllable operating conditions, and is suitable for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a scanning electron microscope image of boron nitride modified copper ferrite (CFBN10), copper ferrite (CuFe2O4) and boron nitride (BN) prepared in Example 1 of the present invention.

[0024] Figure 2 X-ray diffraction patterns of boron nitride modified copper ferrite (CFBN5, CFBN10, CFBN15, CFBN20), copper ferrite (CuFe2O4) and boron nitride (BN) prepared in Example 1 of the present invention.

[0025] Figure 3 IR spectra of boron nitride modified copper ferrite (CFBN5, CFBN10, CFBN15, CFBN20), copper ferrite (CuFe2O4) and boron nitride (BN) prepared in Example 1 of the present invention.

[0026] Figure 4 This is a diagram showing the degradation effect of boron nitride modified copper ferrite (CFBN5, CFBN10, CFBN15, CFBN20), copper ferrite (CuFe2O4) and boron nitride (BN) activated periodate on oxytetracycline prepared in Example 1 of the present invention.

[0027] Figure 5 This is a graph showing the degradation effect of oxytetracycline on the boron nitride-modified copper ferrite (CFBN10) in Example 2 of the present invention by activating periodate in the presence of different anions.

[0028] Figure 6 This is a graph showing the degradation effect of oxytetracycline on boron nitride-modified copper ferrite (CFBN10) under different pH conditions by activating periodate.

[0029] Figure 7 This is a graph showing the corresponding cycle number-degradation effect when boron nitride-modified copper ferrite (CFBN10) activates periodate to cyclically degrade oxytetracycline in Example 4 of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0031] The raw materials and instruments used in the following examples are all commercially available. In the examples of the present invention, unless otherwise specified, the processes used are conventional processes, the equipment used are conventional equipment, and the data obtained are the average values ​​of three repeated experiments.

[0032] Example 1

[0033] The method for removing oxytetracycline from water by activating periodate with copper ferrite modified by boron nitride is specifically to remove oxytetracycline from water by copper ferrite modified by boron nitride under the condition of activating periodate, comprising the following steps:

[0034] Weigh 25 mg each of boron nitride material (BN), copper ferrite material (CuFe2O4) and boron nitride modified copper ferrite material (CFBN5, CFBN10, CFBN15, CFBN20), and add them to 50 mL of a solution containing oxytetracycline (20 mg / L) (the pH value of the solution is 4.5). Use a circulating cooling device to control the reaction temperature at 25°C. Stir for 30 minutes to allow the catalytic material to reach the adsorption and desorption equilibrium of oxytetracycline. Then, add periodate to make its concentration in the solution reach 1 mM to trigger the catalytic reaction. The reaction is allowed to proceed for 60 minutes to achieve the removal of oxytetracycline in the water.

[0035] Blank control group: Take 50 mL of a solution containing oxytetracycline (20 mg / L), do not add any catalytic material, only add periodate (1 mM), and react under the same conditions as the control.

[0036] During the activation of periodate, 1 mL of the reaction solution was aspirated every 10 minutes, filtered through a 0.22 μm filter head, and then added to 20 μL of sodium thiosulfate solution (concentration of 1 M). Finally, the concentration of oxytetracycline in the solution was detected by high performance liquid chromatography to evaluate the degradation performance of the catalytic material.

[0037] In this embodiment, the boron nitride modified copper ferrite includes boron nitride, copper ferrite and boron nitride modified copper ferrite.

[0038] In this embodiment, the copper ferrite is a three-dimensional nano-spherical structure with a diameter of about 300-500 nm; and the boron nitride is a two-dimensional porous nano-sheet structure.

[0039] In this embodiment, the preparation method of the boron nitride material comprises the following steps: 0.756g of melamine and 0.742g of boric acid are ultrasonically dispersed in 100mL of aqueous solution, and heated and stirred at 80°C to obtain a uniform solution. Then, the above solution is naturally cooled and placed in a refrigerator for 12 hours to precipitate a white solid, which is filtered and collected, and dried to obtain a boron nitride precursor, and the obtained boron nitride precursor is first calcined at 600°C for 3 hours at a heating rate of 5°C / min in a tube furnace, and then calcined at 700°C for 2 hours at a heating rate of 5°C / min to obtain boron nitride (denoted as BN).

[0040] In this embodiment, the preparation method of the copper ferrite material comprises the following steps: 6mmol of copper nitrate trihydrate and 12mmol of ferric nitrate nonahydrate are added to 70mL of ethylene glycol, and stirred under magnetic stirring until completely dissolved to form solution A. 18mmol of anhydrous sodium acetate is added to 20mL of ethylene glycol and stirred until completely dissolved to form solution B. Then, solution B is slowly added dropwise to solution A and stirred under magnetic stirring for 1h until uniformly mixed. Subsequently, the above solution is transferred to a 100mL polytetrafluoroethylene reactor and reacted at 180°C for 18h. After naturally cooling to room temperature, the product is collected by magnet attraction, washed several times with ethanol and deionized water, and the solid finally obtained is dried at 60°C in a vacuum drying oven for 12h to obtain a copper ferrite material (denoted as CuFe2O4).

[0041] In this embodiment, the mass ratio of boron nitride to copper ferrite in the boron nitride modified copper ferrite (CFBN10) is 1:10.

[0042] In this embodiment, the preparation method of boron nitride modified copper ferrite comprises the following steps: weigh 82 mg of the boron nitride prepared above and ultrasonically disperse it in 70 mL of ethylene glycol, then add 6 mmol of copper nitrate trihydrate and 12 mmol of ferric nitrate nine hydrate, and stir under magnetic stirring until completely dissolved to form solution A. 18 mmol of anhydrous sodium acetate is added to 20 mL of ethylene glycol and stirred until completely dissolved to form solution B. Then, solution B is slowly added dropwise to solution A and stirred under magnetic stirring for 1 hour until mixed evenly. Subsequently, the above solution is transferred to a 100 mL polytetrafluoroethylene autoclave and reacted at 180 ° C for 18 hours. After naturally cooling to room temperature, the product is collected by magnet attraction, washed several times with ethanol and deionized water, and the solid finally obtained is dried at 60 ° C for 12 hours in a vacuum drying oven to obtain boron nitride modified copper ferrite (denoted as CFBN10).

[0043] In this embodiment, the preparation method of boron nitride modified copper ferrite (CFBN5) is basically the same as that of boron nitride modified copper ferrite (CFBN10), with the only difference being that the mass ratio of boron nitride to copper ferrite in boron nitride modified copper ferrite (CFBN5) is 1:5.

[0044] In this embodiment, the preparation method of boron nitride modified copper ferrite (CFBN15) is basically the same as that of boron nitride modified copper ferrite (CFBN10), with the only difference being that the mass ratio of boron nitride to copper ferrite in boron nitride modified copper ferrite (CFBN15) is 1:15.

[0045] In this embodiment, the preparation method of boron nitride modified copper ferrite (CFBN20) is basically the same as that of boron nitride modified copper ferrite (CFBN10), with the only difference being that the mass ratio of boron nitride to copper ferrite in boron nitride modified copper ferrite (CFBN20) is 1:20.

[0046] Figure 1 The following are scanning electron microscope images of boron nitride modified copper ferrite (CFBN10), boron nitride (BN) and copper ferrite (CuFe2O4) prepared in Example 1 of the present invention. Among them, (a) is BN, (b) is CuFe2O4, and (c) is CFBN10 composite material. Figure 1 It can be seen that boron nitride is a two-dimensional nanosheet structure, and copper ferrite is a three-dimensional nanosphere structure with a diameter of about 300 to 500 nm. In the CFBN10 composite material, BN nanosheets are uniformly attached to the CuFe2O4 nanospheres.

[0047] Figure 2 The X-ray diffraction patterns of the boron nitride modified copper ferrite (CFBN5, CFBN10, CFBN15, CFBN20), boron nitride (BN) and copper ferrite (CuFe2O4) prepared in Example 1 of the present invention are shown in FIG. Figure 2 It can be seen that all characteristic peaks of CuFe2O4 are well pointed to the cubic phase of CuFe2O4. The characteristic peaks at 2θ=26.2° and 43.5° in the BN sample correspond to the (002) and (101) planes of boron nitride, respectively. The characteristic peaks corresponding to BN and CuFe2O4 can be observed in all boron nitride modified copper ferrites (CFBN5, CFBN10, CFBN15, CFBN20), indicating that the modified materials were successfully prepared.

[0048] Figure 3 The infrared spectra of the boron nitride modified copper ferrite (CFBN5, CFBN10, CFBN15, CFBN20), boron nitride (BN) and copper ferrite (CuFe2O4) prepared in Example 1 of the present invention are shown in FIG. Figure 3 It can be seen that for boron nitride (BN), the -1 and 1074cm -1 The absorption peak belongs to BN or BO bond, 792cm -1 and 3259cm -1 The absorption peaks are the transverse stretching vibrations of BNB and NH. For copper ferrite (CuFe2O4), 581cm -1 and 449cm -1 The two peaks at 3418 cm-1 are the stretching vibrations of Fe-O and Cu-O. In addition, for all samples, there is a -1 It can be seen that the characteristic peaks of BN and CuFe2O4 can be observed in almost all boron nitride modified copper ferrites (CFBN5, CFBN10, CFBN15, CFBN20). In addition, the peak at about 486 cm -1 A new peak was also observed at , which is the characteristic peak of Fe-N bond. The above results confirm that CuFe2O4 and BN form a close chemical coupling structure through Fe-N bond.

[0049] From the above results, it can be seen that the present invention uses boron nitride to modify copper ferrite, realizes the effective loading of copper ferrite on boron nitride nanosheets, and forms a chemical coupling structure connected by Fe-N bonds.

[0050] Figure 4 The figure is a graph showing the degradation effect of boron nitride modified copper ferrite (CFBN5, CFBN10, CFBN15, CFBN20), boron nitride (BN) and copper ferrite (CuFe2O4) on oxytetracycline under activated periodate conditions in Example 1 of the present invention. Figure 4It can be known that the boron nitride modified copper ferrite activated periodate of the present invention has a good degradation effect on oxytetracycline, and the degradation effect is continuously enhanced with the increase of the boron nitride content in the boron nitride modified copper ferrite. When the mass ratio of boron nitride to copper ferrite reaches 1:10 (i.e., CFBN10), the degradation effect on oxytetracycline is optimal. If the mass ratio of boron nitride to copper ferrite is further increased to 1:5 (i.e., CFBN5), the degradation effect of the composite material on oxytetracycline decreases instead. This is because excessive boron nitride reduces the total number of metal active sites of the material and reduces the number of Fe-N interface structures in the material. The mass ratio of boron nitride to copper ferrite is optimally 1:10. Therefore, the boron nitride modified copper ferrite (CFBN10) activated periodate prepared in Example 1 of the present invention has the best degradation effect on oxytetracycline, and can degrade 91.02% (20 mg / L) of oxytetracycline after 60 minutes of activated periodate. The CFBN10 composite material exhibits the best periodate activation performance for the degradation of oxytetracycline, mainly because the modification of boron nitride significantly increases the specific surface area of ​​the composite material, promotes the exposure of active sites on the surface of the material, and forms a chemical coupling structure connected by Fe-N bonds. The increase in the specific surface area of ​​the material can effectively improve the material's adsorption performance for periodate, while promoting the generation of active species such as high-valent metal oxygen species. The interfacial Fe-N bond acts as a charge transfer channel, further accelerating the electron migration of the metal iron center, enhancing the generation rate of active species such as free radicals and high-valent metal oxygen species, and promoting the degradation of oxytetracycline.

[0051] Example 2

[0052] The method for removing oxytetracycline from water by activating periodate with copper ferrite modified by boron nitride comprises the following steps:

[0053] Weigh 6 portions of boron nitride modified copper ferrite (CFBN10), 25 mg each, and add them to a 5 mmol / L SO4 2- 、NO3 - 、CO3 2- 、HCO3 - , Cl - In a 50mL solution containing oxytetracycline (20mg / L) without adding any ions (the pH value of the solution is 4.5), the circulating cooling device controls the reaction temperature at 25°C, and stirs for 30 minutes to allow the catalytic material to reach the adsorption-desorption equilibrium of oxytetracycline. Subsequently, periodate is added to make its concentration in the solution reach 1mM to trigger the catalytic reaction, and the reaction is carried out for 60 minutes to achieve the removal of oxytetracycline in the water.

[0054] During the activation of periodate, 1 mL of the reaction solution was drawn every 10 min, filtered with a 0.22 μm filter head, and added to 20 μL of sodium thiosulfate solution (concentration of 1 M). Finally, the concentration of oxytetracycline in the solution was detected by high performance liquid chromatography to evaluate the degradation performance of oxytetracycline by periodate activated by boron nitride modified copper ferrite (CFBN10) in the presence of different anions. The results are shown in Figure 2. Figure 5 shown.

[0055] Figure 5 The figure is a graph showing the degradation effect of oxytetracycline on the activation of periodate by copper ferrite modified with boron nitride (CFBN10) in the presence of different anions in Example 2 of the present invention. Figure 5 It can be seen that the boron nitride modified copper ferrite (CFBN10) of the present invention can degrade oxytetracycline by activating periodate without adding any ions, and can degrade 91.02% of oxytetracycline (20 mg / L) after 60 minutes. 2- and Cl - In the presence of SO4, the periodate activated by boron nitride modified copper ferrite (CFBN10) had no significant inhibitory effect on the degradation of oxytetracycline, indicating that SO4 2- and Cl - The presence of CO has little effect on the degradation of oxytetracycline. 2- 、HCO3 - and NO3 - In the presence of boron nitride modified copper ferrite (CFBN10), periodate activated has a certain inhibitory effect on the degradation of oxytetracycline, but still has a high degradation performance. The decrease in the catalytic activity of periodate is partly due to the fact that CO3 2- 、HCO3 - and NO3 - It can act as a free radical scavenger, combining with strong active free radicals to generate relatively weak active substances, resulting in a decrease in the degradation performance of oxytetracycline. On the other hand, due to CO3 2- and HCO3 - The addition of will cause the pH of the solution to increase, resulting in part of the periodate being converted or polymerized into iodine species with a lower reduction potential, thereby producing fewer active species to act on the degradation of oxytetracycline.

[0056] Example 3

[0057] The method for removing oxytetracycline from water by activating periodate with copper ferrite modified by boron nitride comprises the following steps:

[0058] Weigh 5 portions of boron nitride modified copper ferrite (CFBN10), 25 mg each, and add them to 50 mL of a solution containing oxytetracycline (20 mg / L) at pH values ​​of 3.0, 7.0, 9.0, 11.0 and without adjusting the pH (the pH value of the solution is 4.5). The reaction temperature is controlled at 25°C by a circulating cooling device. Stir for 30 minutes to allow the catalytic material to reach the adsorption-desorption equilibrium of oxytetracycline. Subsequently, periodate is added to make its concentration in the solution reach 1 mM to trigger the catalytic reaction. The reaction is carried out for 60 minutes to achieve the removal of oxytetracycline in the water.

[0059] During the activation of periodate, 1 mL of the reaction solution was drawn every 10 min, filtered with a 0.22 μm filter head, and added to 20 μL of sodium thiosulfate solution (concentration of 1 M). Finally, the concentration of oxytetracycline in the solution was detected by high performance liquid chromatography to evaluate the degradation performance of oxytetracycline by periodate activated by boron nitride (CFBN10) under different pH conditions. The results are shown in Figure 2. Figure 6 shown.

[0060] Figure 6 The figure is a graph showing the degradation effect of oxytetracycline on the activation of periodate by boron nitride modified copper ferrite (CFBN10) under different pH conditions in Example 3 of the present invention. Figure 6 It can be seen that the boron nitride modified copper ferrite (CFBN10) of the present invention has a high degradation effect on oxytetracycline under natural conditions by activating periodate, and can degrade 91.02% of oxytetracycline (20 mg / L) after 60 minutes. However, the degradation effect of oxytetracycline is reduced under alkaline conditions. The degradation effect of oxytetracycline is low when the pH is 11.0 because part of the periodate is converted or polymerized into iodine species with a lower reduction potential, thereby affecting the catalytic performance. On the contrary, the degradation of oxytetracycline is accelerated under acidic conditions. In particular, when the pH value of the solution is 3.0, 94.29% of oxytetracycline (20 mg / L) can be degraded within 60 minutes. The enhancement of the catalytic effect under acidic conditions is due to the fact that H + The presence of promotes the generation of active species. However, it can be seen that in the weakly acidic range (pH 3-7), the periodate catalytic performance of the catalyst is the best. Since most actual water bodies are weakly acidic, the boron nitride modified copper ferrite in the present invention has a wide range of applicability.

[0061] Example 4

[0062] Boron nitride modified copper ferrite activates periodate to degrade the stability of oxytetracycline in water, comprising the following steps:

[0063] (1) Weigh 25 mg of boron nitride modified copper ferrite (CFBN10) and add it to 50 mL of a solution containing oxytetracycline (20 mg / L) (the pH value of the solution is 4.5). The reaction temperature is controlled at 25 °C by a circulating cooling device. Stir for 30 min to allow the catalytic material to reach an adsorption-desorption equilibrium for oxytetracycline. Then, periodate is added to make its concentration in the solution reach 1 mM to trigger the catalytic reaction. The reaction is allowed to proceed for 60 min to achieve the removal of oxytetracycline in the water.

[0064] (2) During the activation of periodate, 1 mL of the reaction solution was aspirated every 10 min, filtered through a 0.22 μm filter head, and then added to 20 μL of sodium thiosulfate solution (concentration of 1 M). Finally, the concentration of oxytetracycline in the solution was detected by high performance liquid chromatography to evaluate the degradation performance of boron nitride modified copper ferrite (CFBN10) activated with periodate on oxytetracycline.

[0065] (3) After each reaction, the catalyst was collected by a magnet. Then, the catalyst was washed several times with deionized (DI) water and 70% ethanol solution, resuspended in ethanol solution, treated with ultrasound for 30 min, and finally collected again by a magnet. This step was repeated three times to dissolve and remove oxytetracycline adsorbed on the catalyst surface. The collected material was dried at 60 °C under vacuum conditions.

[0066] (4) Steps (1) to (3) were repeated five times to investigate the stability of the degradation of oxytetracycline by periodate activated by boron nitride modified copper ferrite (CFBN10). Figure 7 shown.

[0067] Figure 7 The graph is a graph showing the number of cycles corresponding to the degradation effect when copper ferrite modified by boron nitride (CFBN10) is activated by periodate to cyclically degrade oxytetracycline in Example 4 of the present invention. Figure 7 It can be seen that after five cycles, the boron nitride modified copper ferrite (CFBN10) still exhibits a high oxytetracycline degradation performance, which shows that the boron nitride modified copper ferrite of the present invention has the advantages of stable catalytic performance, strong corrosion resistance, and high oxytetracycline degradation efficiency. It is a new type of composite catalytic material with high degradation performance and good repeatability.

[0068] The above embodiments are preferred implementation modes of the present invention, but the protection scope of the present invention is not limited to the above embodiments. Any other changes, modifications, combinations, substitutions and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for removing oxytetracycline from water by activating periodate with copper ferrite modified by boron nitride, characterized in that: Boron nitride modified copper ferrite is used to activate periodate to degrade oxytetracycline in water; the boron nitride modified copper ferrite is based on copper ferrite as a base material, and boron nitride is modified on the copper ferrite; the mass ratio of boron nitride to copper ferrite in the boron nitride modified copper ferrite is 1:5-20; preferably, the copper ferrite is a three-dimensional nano-spherical structure with a diameter of about 300-500nm; the boron nitride is a two-dimensional porous nano-sheet structure.

2. The method for removing oxytetracycline from water by activating periodate with boron nitride-modified copper ferrite according to claim 1, characterized in that: The method uses boron nitride modified copper ferrite to activate periodate to degrade oxytetracycline in water, comprising the following steps: mixing the boron nitride modified copper ferrite with water containing oxytetracycline, carrying out oxytetracycline degradation reaction under the condition of adding periodate, and completing the degradation of oxytetracycline in the water; the addition amount of the boron nitride modified copper ferrite is 0.3g to 0.7g of the boron nitride modified copper ferrite per liter of oxytetracycline solution.

3. The method for removing oxytetracycline from water by activating periodate with boron nitride-modified copper ferrite according to claim 1 or 2, characterized in that: The water body contains oxytetracycline (OTC); the concentration of the water body containing oxytetracycline is 5-25 mg / L; the pH value of the water body containing oxytetracycline is 3.0-11.0; the periodate in the degradation experiment is sodium periodate (NaIO4); the concentration of the periodate in the degradation experiment is 0.4-1.2 mM; the time for the catalyst to reach adsorption and decomposition equilibrium is 30-60 minutes; and the reaction time of the degradation experiment is 0-60 minutes.

4. The method for removing oxytetracycline from water by activating periodate with boron nitride-modified copper ferrite according to any one of claims 1 to 3, characterized in that: The method for preparing the boron nitride modified copper ferrite comprises the following steps: S1. Dispersing boric acid and melamine in a beaker filled with deionized water, heating and dissolving, and stirring to obtain a uniform solution; then placing the solution in a refrigerator to precipitate a white solid, filtering and collecting the white solid, and further drying to obtain a boron nitride precursor; then, calcining the obtained boron nitride precursor twice in a tubular furnace to obtain boron nitride; S2, ultrasonically dispersing the boron nitride obtained in step S1 in ethylene glycol, and further stirring to obtain a uniform suspension; then adding copper nitrate trihydrate and ferric nitrate nonahydrate to the above suspension, stirring until completely dissolved, to obtain a transparent reddish brown solution A; dissolving anhydrous sodium acetate in ethylene glycol and stirring to form a white solution B; then, dripping solution B dropwise into the stirred solution A, and further stirring to obtain solution C; finally, transferring the above solution C to a polytetrafluoroethylene reactor for hydrothermal reaction, and separating, washing, and drying the reaction product to obtain a precursor of boron nitride-modified copper ferrite; S3, placing the precursor of the boron nitride modified copper ferrite obtained in step S2 in a muffle furnace for calcination to obtain a boron nitride modified copper ferrite.

5. The method for preparing boron nitride modified copper ferrite according to claim 4, characterized in that: In step S1: the ratio of melamine, boric acid and water is 0.756g:0.742g:100mL; the ultrasonic time is 30-60min; the heating temperature is 80-90°C; the stirring is carried out at a rotation speed of 500r / min-800r / min; the refrigeration temperature is 0-4°C; the drying treatment is carried out at a temperature of 60°C-80°C; the drying treatment time is 8h-12h; the calcination is carried out under N2 atmosphere; the first calcination temperature is 600°C, the calcination heating rate is 5°C / min, and the calcination time is 3h; the second calcination temperature is 700°C, the calcination heating rate is 5°C / min, and the calcination time is 2h.

6. The method for preparing boron nitride modified copper ferrite according to claim 4, characterized in that: In step S2, the mass ratio of boron nitride to stoichiometric copper ferrite is 1:5-20; the ultrasonic time of solution A is 30-60 min; the ratio of copper nitrate trihydrate, ferric nitrate nonahydrate, anhydrous sodium acetate, and ethylene glycol in solution C is 1 mmol:2 mmol:3 mmol:15 mL; the stirring time is 30-60 min, and the stirring is carried out at a rotation speed of 500 r / min-800 r / min; the ratio of ethylene glycol content in solutions A and B is 7 mL:2 mL; the stirring time is 30-60 min, and the stirring is carried out at a rotation speed of 500 r / min-800 r / min; the temperature of the hydrothermal reaction is 180-200° C., and the hydrothermal reaction time is 18 h; the solid separation method is magnetic precipitation separation; the drying treatment is carried out at a temperature of 60° C.-80° C.; and the drying treatment time is 8 h-12 h.

7. The method for preparing the boron nitride modified copper ferrite catalyst material according to claim 4, characterized in that: In step S3, the calcination temperature is 400-450°C, the calcination heating rate is 5°C / min, and the calcination time is 2-3h.

8. A boron nitride modified copper ferrite material obtained by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Magnetic carbon-doped spinel copper ferrite catalyst as well as preparation method and application thereof

    CN113856680A

  • Preparation of boron nitride material anchored cobalt ferrite composite catalyst and application of boron nitride material anchored cobalt ferrite composite catalyst in catalytic degradation of oxytetracycline

    CN114471654A

  • Method for degrading acetaminophen in water body by using carbon-doped boron nitride activated periodate

    CN117735696A

  • Cu-BNC catalyst with double active sites as well as preparation method and application of Cu-BNC catalyst

    CN117797845A

  • Method for preparing copper ferrite / zeolite spinel composite material and use thereof

    WO2021136228A1

Cited By

  • Method for rapidly oxidizing and degrading antibiotics in water through high-frequency ultrasonic activation of permanganate / periodate

    CN120247158A

  • Method for degrading antibiotics by activating periodate through layered bismuth-based perovskite heterojunction

    CN121134957A